Marrying Unwanted Pregnant Girl Phenomenon in Indonesia: Is it in the Child's Best Interests? - Sundari, Elisabeth; Retnowati, Anny (KnE Social Sciences, 2024)
This research aims to examine the dynamic meaning of ’the best interests of the child’ in Indonesia’s phenomenon of marrying unwanted pregnant girls. Using normative legal research, the data compiled on the parent’s reason and the judges’ considerations in granting child marriage at Wonosari Religious Court in four latest years (2019-2022). The results indicate that parents and partners tend to propose child marriage dispensation rather than preventing it, in case the partner is already pregnant. The primary reasons of the parent, such as religious principles, protecting the fetus, and the family’s good name, dominantly color the meaning of ’the best interest of the child’. These reasons were well supported by the judges.. This research contributes to the finding that external factors, such as local culture and religion, can influence the dynamic meaning of ’the best interests of the child.’ Keywords: best interest, child marriage, local cultures, religious, unwanted pregnant